Reach, experience, and acceptability of an abortion self-care intervention in Bolivia: a mixed-methods evaluation - Valerie N. Acre; Stephanie Andrea Küng; Christiam Arce; Adela Yapu; Delmy Iriondo; Malena Morales (Sexual and Reproductive Health Matters)
In 2018, Ipas Bolivia launched an abortion self-care (ASC) community intervention with the goal of increasing access to supportive, well-informed abortion support provided by community agents (CAs). Between September 2019 and July 2020, Ipas conducted a mixed-methods evaluation to assess the reach, outcomes, and acceptability of the intervention. We used logbook data maintained by CAs to capture demographic characteristics and ASC outcomes of people supported. We also conducted in-depth interviews with 25 women who had received support and 22 CAs who had provided support. 530 people accessed ASC support through the intervention, most of whom were young, single, educated women accessing abortion in the first trimester. Among the 302 people who self-managed their abortions, 99% reported having a successful abortion. No women reported adverse events. All women interviewed expressed satisfaction with the support provided by the CA and, in particular, with the information, lack of judgement, and respect they felt from CAs. CAs spoke highly about their experience and viewed their participation as a way to increase people’s ability to exercise their reproductive rights. Obstacles included experiences of stigma, fears of legal repercussions, and difficulties dispelling misconceptions around abortion. Legal restrictions and abortion stigma continue to complicate access to safe abortion, and findings from this evaluation highlight important avenues for the effectiveness and expansion of ASC interventions, including legal support to people who have abortions and those who provide abortion support, building capacity of people as informed buyers, and ensuring that interventions reach rural and other often under-served people.